Nosná konstrukce víceúčelové budovy - Hetmer, Jakub (Vysoké učení technické v Brně. Fakulta stavební, 2015)
Diplomová práce „Nosná konstrukce víceúčelové haly“ je zpracována ve formě projektové dokumentace dle platných předpisů. Zabývá se statickým řešením monolitické konstrukce objektu administrativní budovy České spořitelny. Předmětem řešení je návrh železobetonové monolitické bodově podepřené stropní desky, sloupů a schodiště.

This master´s thesis“ Load-bearing Structure of Multi-purpose Building“ is processed in the form of project documentation according to applicable regulations. It deals with static solution of monolitic reinforced concrete construction of administrative building of Česká spořitelna. Subject of the solutions is reinforced concrete monolithic point – supported ceiling slab, columns and staircase.
Load-bearing Structure of Multi-purpose Building
Keywords: Železobetonová monolitická bodově podepřená stropní deska; nosná konstrukce; železobetonový monolitický sloup; schodišťová deska.; Reinforced concrete monolithic point – supported ceiling slab; supporting structure; reinforced concrete monolithic column; stairecase slab